Tetracus daamsi, nueva especie de Galericinae (Erinaceidae, Mammalia) del Oligoceno de Mallorca (Espana). - Hugueney, Marguerite; Adrover, Rafael (Coloquios de Paleontología, 2003)
A new species of Galericinae (Erinaceidae, Mammalia), T. daamsi is described from the Early Oligocene localities of Paguera (Majorca, Spain). It differs from the unique species of Tetracus known hitherto, T. nanus, by a lengthening and a widening of the anterior teeth, probably correlated with a change of feeding habits that could indicate a geographic isolation.